PENERAPAN MODEL PEMBELAJARAN TALKING STICKPADA PEMBELAJARAN IPSKELAS VIII SMPNEGERI 23 PONTIANAK - Krisma Haryuniati; Sri Buwono; Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of study was to find the result of learning model application of Talking Stick learning model in social science for grade 8th students of SMP Negeri 23 Pontianak.The method used in study was Experiments with of the Quasi Experimental Design and Nonequivalent Control Group Design. The study sample was 67 students. Data collection techniques are through observation, measurement, and documentary study. Data collection tool used learning result test and observation sheet. The result using Talking Stick learning model on social studies the average  of 79.435 and the average  of 75.887 using conventional learning models on social studies grade 8th. The results of the t-test using Indenpenden Samples Test (-1.905<2.000) are in the reception area Ho. Student learning outcomes there was no difference between the learning model of talking stick and conventional models. The results of the average score of the first and second post-test meetings in the experimental class and control there were differences. So was not significant difference between learning result of students experiment using learning model talking stick and using conventional model. The effect size of the talking stick learning model on social science learning, grade 8th amounted to 0.452 in the medium category.Keywords: Learning Result, Social Science Learning, Talking Stick Learning Model